Investigation and strategy of intelligent controller (ACBIC) for DC link control in SAPF system for industrial power systems. (2nd January 2021) - Balasubramaniam, P. M.; Sudhakar, S.; Krishnamoorthy, Sujatha; Sriram, V. P.; Dhanaraj, S.; Subramaniyaswamy, V.
Abstract: This article describes the design of the ant colony based fuzzy controller for shunt active power filter is to mitigating harmonics, which is injected by nonlinear loads such as thyristor and rectifies loads. Principally, The design of an ant colony based intelligent controller (ACBIC) designed according to Fuzzy rules, so the system is robust. The optimized membership function and gain of the controller are normalized by the ant colony algorithm and the fine-tuning of the associated activities and stabilization advantages achieved with Ant Colony Optimization (ACO). The simulation results presented and model outcomes demonstrate the best dynamic performance and control operation compared with the classical PI Controller. The optimized PI controller gives a better performance during the high transient time, and it minimizes the settling time. Also, the controller bringing down the harmonics and maintains a good quality of power.